CoS2 Nanospheres Anchored on 3D N-Doped Carbon Skeleton Derived from Bacterial Cellulose for Lithium-Sulfur Batteries. Issue 2 (3rd February 2021) - Wang, Shuhui; Guo, Jinze; Guo, Ruisong; Sun, Xiaohong; Li, Fuyun; Li, Tingting; Zhao, Xinqi; Luo, Yani
Abstract : To address sluggish sulfur redox kinetic and the "shuttling behavior" of polysulfides in lithium-sulfur batteries (LSBs), CoS2 hollow nanospheres tightly anchored on three-dimensional (3D) N-doped biological carbon nanofibers skeleton (CoS2 /N-CNFs) are successfully designed as highly-efficient sulfur hosts. The carbon nanofibers obtained by carbonization of bacterial cellulose are interweaved with each other, and can provide a firm 3D conductive skeleton for the low-conductive sulfur cathode. And the N-doping carbon nanofibers skeleton with polar CoS2 can achieve synergetic physical/chemical adsorption of polysulfides and effective catalytic conversion, which are contributed to enhance sulfur redox kinetic and effectively suppress the shuttling effect. Moreover, the skeleton with abundant −OH functional groups achieve strong chemisorption to CoS2, greatly maintaining structural stability during cycling process. Benefitting from the above-mentioned merits, CoS2 /N-CNFs@S electrode with high sulfur loading of 74.4% exhibits superior reversible capacity of 497.3 mAh g −1 at 0.2 C after 100 cycles with an improved coulombic efficiency of approximately 100%, and the electrode has excellent cycle life with 73% capacity retention over 300 cycles at 0.5 C. This synthesis strategy makes a leading exploration for the application of biological carbon materials in advanced LSBs.